Fast competitive swimmers demonstrate a diminished diving reflex - Fujii, N.; Ishii, Y.; Moriyama, S.; Matsutake, R.; Sengoku, Y.; Nishiyasu, T. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Competitive swimmers complete 50-m front crawl swimming without breathing or with a limited number of breaths. Breath holding during exercise can trigger diving reflex including bradycardia and diminished active muscle blood flow, whereas oxygen supply to vital organ such as brain is maintained. We hypothesized that swimmers achieving faster time in 50-m front crawl with limited number of breaths demonstrate a blunted diving reflex of cardiac and active muscle blood flow responses with elevated cerebral perfusion to counteract peripheral and central fatigues. Twenty-eight competitive swimmers (12 females) underwent a 50-m front crawl swimming time trial with minimum respiratory interruptions, following which they were categorized into two groups: Fast (n = 13) and Slow (n = 15). Additionally, they performed knee extension exercises with maximal voluntary breath- holding, wherein leg blood flow (Doppler ultrasound), cardiac output (Modelflow), heart rate (electrocardiogram), and middle cerebral artery mean blood velocity (transcranial Doppler ultrasound) were evaluated. The pattern of leg blood flow response differed between the two groups (p = 0.031) with the Fast group experiencing a delayed onset of reductions in leg blood flow (p = 0.035). The onset of bradycardia was also delayed in the Fast group (p = 0.014), with this group demonstrating a higher value of the lowest heart rate (between-trial difference in average: 15.9 [3.73, 28.2] beats/min) and cardiac output (between-trial difference in median: 2.84 L/min) (both, p = 0.013). Middle cerebral artery mean blood velocity was similar between the groups (all p = 0.112). We show that swimmers with superior performance in 50-m front crawl swim with limited breaths display a diminished diving reflex.